2014
DOI: 10.1007/s11130-014-0432-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soy Protein and Calcium Levels on Mineral Bioaccessibility and Protein Digestibility from Enteral Formulas

Abstract: Enteral formulas (EF) are complex food systems which have all the nutrients in their matrix for the complete human nourishment. However, there are components in EF which can interact with minerals, reducing their absorption, and thereof the EF nutritional quality. The effect of soy protein (SP) and Ca content on Fe, Zn, and Ca bioaccessibility and protein digestibility (%DP) was assessed using a response surface design in EF. Tested SP levels were 2.5-5.0 g/100 mL of total protein. Ca levels were adjusted with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…However, Astawan et al found that consuming tempeh and soybean flour as a source of protein did not significantly alter the body's ability to absorb calcium [ 19 ]. Moreover, Galán & Drago showed that the mineral bioaccessibility of soy products decreased with increasing soy protein concentration [ 20 ]. Thus, in response to the contradictory findings of earlier research, this study aimed to determine how eight weeks of oral supplementation of isoflavones and L. acidophilus affected calcium status, selected bone cells, and biochemical parameters in healthy female rats.…”
Section: Introductionmentioning
confidence: 99%
“…However, Astawan et al found that consuming tempeh and soybean flour as a source of protein did not significantly alter the body's ability to absorb calcium [ 19 ]. Moreover, Galán & Drago showed that the mineral bioaccessibility of soy products decreased with increasing soy protein concentration [ 20 ]. Thus, in response to the contradictory findings of earlier research, this study aimed to determine how eight weeks of oral supplementation of isoflavones and L. acidophilus affected calcium status, selected bone cells, and biochemical parameters in healthy female rats.…”
Section: Introductionmentioning
confidence: 99%
“…An earlier study with a diet consisting of cereals and legumes characterized by a total of 1% phytic acid resulted in very low iron absorption; but, decreasing the phytic acid by 90% increased the absorption by 2 to 5-fold [21]. Another evidence testifies that a negative influence of soy protein supplement in the absorption of iron, zinc and calcium may not only be due to increased level of phytic acid but also due to trypsin inhibitor in the soy protein [24]. In comparison to plant protein supplements (vegetables), animal protein supplement promotes better dietary minerals absorption, probably due to the quality of protein, which is dependent on the amino acid composition [21,22,23].…”
Section: Results and Discussion 41 In-vitro Bioavailability Of Mineralsmentioning
confidence: 96%
“…Maior simplicidade e adequação a qualquer laboratório Os testes in vitro têm sido amplamente utilizados na determinação da bioacessibilidade de macronutrientes como carboidratos (Bellmann et al, 2018), proteínas (Galán, & Drago, 2014) e lipídeos (Grassby et al, 2017). Assim como, na determinação de micronutrientes, como sais minerais, vitaminas e oligoelementos (Tan et al, 2019;Bryszewska et al, 2019;Souza et al, 2018;Intawongse et al, 2018;Berenguel et al, 2018), compostos secundários de plantas, incluindo carotenoides (Costa & Mercadante, 2018;Rodrigues et al, 2016) e polifenóis (Pešić et al, 2019;Heras et al, 2017;Stanisavljevi´c et al, 2015), bem como para estudar contaminantes em solos (Rodrigues et al, 2018;Foulkes, et al, 2016;Wragg et al, 2011).…”
Section: Modelos De Digestão In Vitro Estáticos Modelos De Digestão I...unclassified